Representation of Underrepresented Group: A Case of Women Political Participation (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Ge n d e r i n e q u a l i t i e s p e r s i s t i n t h e  society, particularly in politics, and their  underrepresentation is widely seen in higher  level positions. The purpose of the study is to  briefly examine broad causes, effect of women  participation in politics and remedies for due  representation. Through academic literature  in the area of economics and political science  with specific concern about gender inequalities  and women’s underrepresentation in politics is  globally realized. Further, extensive secondary  tools applied to establish factors responsible  for women’s underrepresentation, women  positive effects in politics and an effective  system for their redressal. It is observed that  still a misconception existing in the society  that women are incompetent to handle core  areas of administration like finance, economic  development, foreign affairs, defense, trade,  and entrepreneurship with particular reference  to political and government machinery where  women allocate portfolios limited to women-only  issues. It is seen that reserving seats for women  in politics yield positive outcomes. Furthermore,  even after quotas were discontinued, quotas  improved perceptions about women as leaders,  increased girls’ aspirations, and helped women  get elected. In a true democracy, women’s  political participation is a precondition for  realizing gender equality. However, globally,  less than 25 per cent of seats are represented  by women in parliament and only 12 per cent  of women occupy head of state positions. This  disparity is also found in local government in  various countries.
Keywords: women; gender; inequality; gender gap; policy; empowerment